KESESUAIAN MATERI PEMBELAJARAN DENGAN KOMPETENSI DASAR PADA BUKU TEMATIK TEMA 3 KELAS IV SEKOLAH DASAR EDISI REVISI 2017 - Ade Septiani; Vina Amilia Suganda M (Jurnal Inovasi Sekolah Dasar, 2021)
This study aims to determine the suitability of learning materials with basic competencies in the thematic book theme 3 class IV SD revision edition 2017. The research method used is the descriptive qualitative method. The subjects of this study were thematic books on the theme of 3 grade IV SD as well as class teachers and one of the fourth-grade students from SDN 99 OKU. The data collection techniques used were documentation and interviews. In this study, an analysis was carried out covering 3 domains, namely, affective, cognitive, and psychomotor domains. In the affective domain, the data collection technique used interviews, while the cognitive and psychomotor domains used the documentation study by analyzing the 2 aspects analyzed. Based on the results of interviews with teachers and students to see the level of suitability in the affective domain, which is very appropriate. As for the results of the analysis of the level of conformity between the learning material and basic competencies in the cognitive and psychomotor domains as a whole, from the 2 aspects analyzed, the results are included in the very appropriate category. Thus it can be concluded that the suitability of the learning material with the basic competencies in the theme book 3 for grade IV SD revision edition 2017 is very appropriate. Keywords: suitability, learning material, basic competencies, thematic book theme 3